Edukasi isi piringku dan Demo Masak Sea Dimsum Sumber Protein Hewani pada Anak Sekolah di Panti Asuhan Gotong Royong - Fayasari, Adhila; Zahrani Astuti, Elsa; Yasfa Aulia, Hunalika; Yudhowanti, Septiajati; Harjito, Zaneta; Assyifa, Aulia; Salsabila, Delia (Yayasan Inspirasi El Burhani, 2025)
Introduction: Adolescents are vulnerable to nutritional issues such as undernutrition and overnutrition, which can affect their physical and cognitive development. Balanced nutrition is essential, particularly for children in orphanages, who often face challenges in accessing nutritious food and health education. Objective: This community service aimed to improve knowledge and awareness about